The Effect of E-Bupot Unification on Corporate Taxpayer Compliance in The Implementation of Tax Obligations in Jabodetabek - Hubertus Maria Rosariandoko wijanarko; Afton Triadi (Journal of E-business and Management Science, 2023)
This research aims to determine the factors of e-Bupot Unification and socialization and understanding that influence the level of the corporate taxpayer in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). This research consists of three variables, two independent variables, and one dependent variable. The data distributed is primary data in the form of a questionnaire and secondary data obtained from corporate taxpayers in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek). The Statistical method used was multiple regression analysis, a sample of 206 respondents was obtained. The research results show that the variables e-Bupot Unification (X1), Socialization, and Understanding (X2), and have a significant effect on Tax Payer Compliance (Y)